Physical Activity Levels, Perceived Body Appearance, and Body Functioning in Relation to Perceived Wellbeing Among Adolescents - Sollerhed, Ann-Christin; Fransson, Johanna; Skoog, JIsabelle; Garmy, Pernilla (Frontiers in Sports and Active Living, 2022)
This study aimed to investigate self-reported physical activity levels, perceived body appearance, and body functioning in relation to perceived wellbeing among adolescents. A cross-sectional survey was performed in four upper secondary schools in one municipality in southern Sweden. Data were obtained from questionnaires completed by 1,491 adolescents (55.4% females; median age 16; range 15–17 years) during school hours. The participation rate was 71.4%. Logistic regression analyses were carried out with wellbeing as the dependent variable. The independent variables included gender, perceived family financial situation, perceived body appearance, perceived body function, and physical activity level. Perceived positive wellbeing was associated with being satisfied with their body's appearance (OR 3.4; CI 2.6–4.4) and function (OR 3.1; CI 2.2–4.2), being physically active three or more times per week (OR 1.5; CI 1.1–2.0), and a good perceived family financial situation (OR 3.3; CI 1.6–6.7). Gender was not significantly associated with wellbeing. A positive body image, which include both body appearance and body function, and high physical activity levels were significantly associated with wellbeing in adolescents, corroborating the importance of promoting physical activity among younger populations.